Authentic Learning Though Role Play in Learning Financial Reporting : Malaysian Undergraduate Perspective - Damien, Lee; Sharon, Cheuk; Esmie, Obrin Nichol (Human Resource Management Academic Research Society, 2020)
This paper examines whether role-playing provides student with learning opportunities in financial reporting and motivates student to reflect the practical financial reporting issues. The research is conducted in Advance Financial Reporting class under an undergraduate accounting program in a public university during semester two in 2019. The participants were divided into two roles within the context of an audit firm, audit associate and audit supervisor in preparing and reviewing the consolidation of financial statements audit working paper (financial reporting). The results of the study show that role-playing allowed students to improve their knowledge and increase their confidence in preparing consolidated financial statements. It also motivates student to reflect the practical financial reporting issues. Hence, the results suggest that role-play model can be applied to other accounting learning activities with inter-related subjects within accounting.